WRF Model Application to Analyze Factors Affecting Tropical Cyclone Forecasting in the Gulf of Thailand - Hammachukiattikul, Porpattama (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 1 (2019): January - March 2019, 2019)
This paper studies the factors affecting tropical cyclones forecasting in the Gulf of Thailand. The Weather Research and Forecasting (WRF) model is used for the simulation of tropical cyclones. The most interesting case is the formation of Typhoon Gay (8929) on 31 October 1989, which caused extensive losses in lives and property. A 30-year reanalysis dataset from the European Center for Medium-Range Weather Forecasts (ECMWF) and the National Centers for Environmental Prediction (NCEP) indicates that cold surges during the northeastern monsoon played an important role in the formation and WRF model simulation of Typhoon Gay. The results showed that Typhoon Gay had a lower intensity than that calculated from using tropical cyclone wind observations. A Rankin vortex initialization (i.e., a TC bogus technique) was applied for the adjustment of u-v winds in the tropical cyclone by defining parameters in the tropical cyclone (e.g., a radius of 350 km and a wind speed of 186 kt), which provided strong wind speeds. The three experiment cases are 1) changes in u-v wind at 1 level (925 hPa), 2) changes in u-v wind at 3 levels (925, 850, and 500 hPa), and 3) changes in u-v wind at 6 levels (1000, 925, 850, 700, 600, and 500 hPa). This paper compares these results with those for maximum wind speed from the Regional Specialized Meteorological Center (RSMC), which were calculated at 6 u-v wind adjustment levels given maximum wind speeds similar to those in the RSMC data. From this analysis, the influence of cold surges from northeast monsoons during the formation and intensification of tropical cyclones in the Gulf of Thailand was determined. Keywords: Tropical Cyclone, WRF Model, Winter Monsoon Cold Surge, Forecast, the Gulf of Thailand